High-performance work system or “wolf in sheep’s clothing?” a mediating effect of organisational cynicism and its outcome - Baig, Javeria; Elmabrok, Ali Abusalah; Ng, Kim-Soon; Ahmad, Abd Rahman (American Scientific Publishers, 2018)
Cynicism is new developing pattern of employer–employee relations. Current academicians realise the profound effect which cynicism can have on organisations, this significance of understanding the seemingly widespread organisational phenomenon. This study takes a systematic view in which organisational cynicism considered as negative attitude directed, particularly towards the educational sector. The current study aimed to endeavours to examine the mediating role of organisational cynicism on high-performance work system with the outcome of organisational citizenship behaviour among teachers of the public schools in Malaysia. The current study will show the work environmental factors and personal characteristics in determining organisational cynicism and will suggest the causes and consequences of cynicism.